THE PROFIT OF THE PRE-EMPLOYMENT PROGRAM JOCKEY IN THE PERSPECTIVE OF SHARIA ECONOMIC LAW - Firdaus, Beni; Helfi, Helfi; Busyro, Busyro; Hendri, Hendri (Ulul Albab: Jurnal Studi Islam, 2022)
Pre-employment program jockey is an agent who seeks a job for the community and obtains a fee from the services. The practice is particularly carried out related to the pre-employment card program launched by the government in 2020. This article describes the practice of pre-employment jockey and to analyze sharia economic law review on the profit. This article implemented qualitative research. The primary data were obtained through interview, observation and documentation, while the analysis was conducted descriptively. The research reveals that the jockey practice has assisted people to register pre-employment card program in 2020. The assistance consisted of account registration, training, and filling survey. The incentive given to the approved people is IDR 3.550.000 but the transparency about the exact number is not precisely informed to the account owner. It can be more than the said amount or, even worse, the jockey got more incentive. This is inappropriate in sharia economic law. Ijarah principles are not applied here because there is no transparency, the willingness of account owner and justice; instead, the service contains ghulûl (corruption) and gharâr (scam) done by the jockey since what they did can be included as treason.